2001
DOI: 10.2174/0929867013373877
|View full text |Cite
|
Sign up to set email alerts
|

AMPA Receptor Antagonists

Abstract: AMPA Receptor antagonists have received considerable attention in recent years. Within the class of excitatory amino acid receptor antagonists AMPA receptor antagonists have shown excellent neuroprotection in several models of cerebral ischemia and neuronal injury. However, poor physical properties have been a major limiting factor in developing these as viable drug candidates. The quinoxaline-2,3-dione template has been the backbone of various competitive AMPA receptor antagonists such as NBQX, PNQX, YM-90K a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
35
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 0 publications
2
35
0
Order By: Relevance
“…[1][2][3] The glutamate system in brain is highly complex and includes multiple interacting receptors, modulating cotransmitters and multisystem synapses (figure 1). Presynaptic, postsynaptic, and astrocytic mechanisms are important to overall excitatory signaling and to unique plasticity mechanisms which are associated with glutamate transmission [4][5][6] ; the 3 compartments (pre-, postsynaptic, and astrocytic) are all candidate systems for pathology in glutamate-related brain diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The glutamate system in brain is highly complex and includes multiple interacting receptors, modulating cotransmitters and multisystem synapses (figure 1). Presynaptic, postsynaptic, and astrocytic mechanisms are important to overall excitatory signaling and to unique plasticity mechanisms which are associated with glutamate transmission [4][5][6] ; the 3 compartments (pre-, postsynaptic, and astrocytic) are all candidate systems for pathology in glutamate-related brain diseases.…”
Section: Introductionmentioning
confidence: 99%
“…These structural requirements are in accordance with those emphasized in the pharmacophore models of the AMPA receptor reported in the literature for the binding of quinoxalinedione and heterocyclic-fused quinoxalinone antagonists. 10,[16][17][18]36) Among the previously reported TQX series, the 7-chloro-4,5-dihydro-4-oxo-8-(1,2,4-triazol-4-yl)-1,2,4-triazolo[1,5-a]quinoxaline-2-carboxylic acid TQX-173 and its corresponding ethyl ester (Fig. 1), both bearing a (1,2,4-triazol-4-yl) moiety at the crucial 8-position, emerged as two of the most active and selective TQX compounds toward the AMPA receptor.…”
mentioning
confidence: 99%
“…27,29) Thus, it can be hypothesized that the 8-heteroaryl group on the TQX framework interacts with a hydrophobic receptor region which also contains a hydrogen bond donor site. 10,[16][17][18]36) Pursuing our studies on the SAR of the TQX series, the 8- Universita' degli Studi di Firenze; Viale G. Pieraccini, 6, 50134 Firenze, Italy. Received December 19, 2007; accepted April 30, 2008; published online May 8, 2008 In this paper, we report a study on some new 4,5-dihydro-4-oxo-1,2,4-triazolo[1,5-a]quinoxaline-2-carboxylate derivatives (TQXs), bearing a nitrogen-containing heterocycle at position-9, and designed as (R,S)-2-amino-3-(3-hydroxy-5-methylisoxazol-4-yl)propionic acid (AMPA) receptor antagonists.…”
mentioning
confidence: 99%
“…In mammalian cells these are key enzymes in the biosynthesis of a variety of bioregulatory compounds such as hydroxyeicosatetraenoic acids (HETEs), leukotrienes, lipoxins and hepoxylines [4]. It has been found that these lipoxygenase products play a role in a variety of disorders such as inflammation [5], tumor angiogenesis [6] and bronchial asthma [7]. LOXs are therefore a potential target for the rational drug design and discovery of mechanismbased inhibitors for the treatment of inflammation, bronchial asthma, cancer and autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%